Identification of GiOMT gene family in Glycyrrhiza inflata bat and expression analysis under UV-B stresses - Caijuan Li; Hao Li; Yufan Liang; Rong Miao; Ziliang Liu; Sijin Chen; Dan Zhang; Cuiling Wang; Jiling Wu; Xiangyan Zhou; Mengfei Li (BMC Genomics)
Abstract Background O-Methyltransferase (OMTs) is a class of conserved multifunctional enzymes that play important roles in plant developmental regulation, hormone signaling, secondary metabolite synthesis and abiotic stress response. The GiOMT gene family has been identified and analyzed in species such as citrus, alfalfa, Populus and grape, but has not been reported in Glycyrrhiza inflata Bat. Results In this study, we systematically identified and analyzed the GiOMT gene family of G. inflata by bioinformatics, and analyzed their physicochemical properties, conserved motifs, conserved structural domains, gene structures, phylogenetic relationships, chromosomal localization and fragment duplications, and the expression patterns of GiOMT genes in combination with transcriptomic data and qRT-PCR. The results showed that a total of 41 GiOMTs were identified in G. inflata, which were named GiOMT1 ~ GiOMT41 based on their chromosomal locations. Protein characterization showed that 29 GiOMT proteins were hydrophilic and 12 GiOMT proteins were hydrophobic. Subcellular predicted localization revealed that most GiOMT proteins localized in the cytoplasm and chloroplasts. Phylogenetic relationships showed that the OMT genes of three species, G. inflata, Arabidopsis and alfalfa, were distributed in three taxa, while the GiOMT genes were distributed in taxa I and II. Promoters of GiOMT genes contained light responsive element and many hormone responsive elements. The expression levels of GiOMT genes under UV-B stress were varied, indicating that GiOMT gene was in response to abiotic stresses in G. inflata. Conclusion In this study, we investigated the genome-wide identification, structure, evolution and expression analysis of the GiOMT gene in G. inflata. The basal sequence of GiOMT genes was highly conserved throughout the evolutionary history of G. inflata. Most of the GiOMT genes were highly expressed in roots and were involved in the response to UV-B stress. The GiOMT genes may lead to the accumulation of flavonoids and enhancement of G. inflata quality and drug activity in G. inflata under UV-B radiation.